A representative assessment of the management of open fractures of the lower limb within UK orthoplastic centres: A two-centre audit of compliance with national standards. Issue 10 (October 2017) - Rymer, B.; Dimovska, E.O.F.; Chou, D.T.S.; Choa, R.; Davis, B.; Huq, S.
Abstract: Background: Open fractures of the lower limb represent a complex and varied array of injuries. The BOAST 4 document produced by BAPRAS and the BOA provides standards on how to manage these patients, and NICE have recently produced additional guidance. We aimed to assess concordance with these standards in a large cohort representative of UK orthoplastic centres. Methods: Patients admitted to the orthoplastic units at Norfolk and Norwich University Hospital and Royal Stoke University Hospital with open lower limb fractures between 2009 and 2014 were included. Data was gathered from notes and endpoints based on the BOAST 4 document. Results: In total, 84 patients were included across the two sites, with 83 having their initial debridement within 24 h (98.8%). Forty-two patients had a documented out-of-hours initial surgery. Of these, 10 (23.8%) had an indication for urgent surgery. This pattern was consistent across both hospitals. A plastic surgeon was present at 33.3% of initial operations. Of 78 patients receiving definitive soft tissue cover, 56.4% had cover within 72 h and 78.2% within 7 days. Main reasons for missing these targets were transfer from other hospitals, plastic surgeons not present at initial operation and intervening critical illness. Conclusions: This study has identified key areas for improving compliance with the national BOAST 4 and NICE standards. Out-of-hours operating is occurring unnecessarily and time targets are being missed. The development of dedicated referral pathways and a true orthoplastic approach are required to improve the management of this complex set of injuries.